National examination of the performance of Dentistry students (ENADE - 2016) - a look at institutions, students, and collective health (Research, Society and Development, 2020)
The National Academic Performance Examination (Enade), one of the evaluation axes of the National Higher Education Assessment System (SINAES), is responsible for evaluating public and private Higher Education Institutions (HEIs), identifying the performance of university students and the characteristics of courses. This analytical observational analytical study aimed to assess the association between the characteristics of HEIs, students and performance in Collective Health issues with the performance at ENADE 2016. The research sample was 205 public and private HEIs of Dentistry in Brazil. The course reports issued by INEP (National Institute of Educational Studies and Research Anísio Teixeira) were analyzed to identify variables related to HEI (location, type, ENADE concept, number of students completing the course and students taking the test); students (color, family income, parental education; type of school attended in high school, degree of difficulty of the test in general and specific training; relation to total time; clarity of statements; difficulty in answering the test) and the performance of students in the test (general and specific SC result). It was found that public HEIs presented a significantly higher mean and variability among students than significantly less than private institutions. It was also noted an association between the performance of ENADE with the students 'family income, parents' education, type of school attended by high school students, number of senior students and students attending the test. It is concluded that, as identified for the general grade of ENADE, students from public HEIs had better performance in the questions that addressed the Collective Health content than those enrolled in private HEIs and that less crowded classrooms and extensive participation of students from evidence should be stimulated.